1991
DOI: 10.1111/j.1460-2695.1991.tb00643.x
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Fatigue Crack Growth in the Fretting‐corrosion‐fatigue of High Tensile Roping Steel in Air and Seawater

Abstract: Fretting fatigue tests of high tensile roping steel, 1 .5 mm in diameter, 1770 MPa grade, were carried out in air and seawater. S-N curves were completed in both the environments and under cathodic protection at -850 mV (SCE). The crack growth curves were determined at three different alternating stress levels. The coefficients of friction between the specimen and the fretting bridge, where the macro-slip occurred, were found to be 0.63 in air and 0.38 in seawater. The prediction of the fretting fatigue lives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Various methodologies are used to evaluate fretting fatigue damage and to predict fatigue life, such as multiaxial fatigue criterion [11] and fracture mechanics approach [22][23][24][25][26][27]. As a fatigue phenomenon, fretting fatigue has the common characters of the plain fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Various methodologies are used to evaluate fretting fatigue damage and to predict fatigue life, such as multiaxial fatigue criterion [11] and fracture mechanics approach [22][23][24][25][26][27]. As a fatigue phenomenon, fretting fatigue has the common characters of the plain fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…The tension-torsion fretting fatigue life of steel wire consists of crack initiation and propagation lives. In fretting fatigue, most of the fatigue life of steel wire is spent propagating the crack since the fatigue crack initiates in the very early stage of the fatigue life (the initiation of fatigue crack occurred approximately at 10-20% of the total life) [2]. Coupled roles of tensile fatigue, torsional fatigue, and fretting wear during tension-torsion fretting fatigue cause the multiaxial stress states at the fretting contact region.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it was found that the degree of electrochemical corrosion and maximum crack depth of fatigue wire were the largest in the acid electrolyte solution. Takeuchi et al [2] studied the behavior of fatigue crack growth in the frettingcorrosion fatigue of high-tensile roping steel in air and seawater and found that the method of removing the electrochemical component was very promising for the prevention of fretting fatigue failure in seawater. Li [8] explored multiaxial fretting fatigue behaviors of steel wires and found larger damage during tension-torsion fretting fatigue as compared to tension-tension fretting fatigue and torsional fretting.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these applications, cyclic loads or deformations are predominant, and consequently it is of primary importance to study the cyclic performance of these ultra high strength steels or, in other words, their fatigue properties. Most of the papers of the available literature on that topic are devoted to high cycle fatigue behaviour of cold drawn pearlitic steel [2][3][4][5][6][7][8][9] and to corrosion fatigue [10][11][12][13][14][15], with some of them focused on the role of the microstructure with respect to the degree of cold drawing on the fatigue life. But few papers are dedicated to fatigue crack propagation and fatigue threshold [16][17][18][19][20], most studies being conducted on wires having a diameter of about 5 to 10 mm [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%